Pengaruh Harga Dan Servicescape Terhadap Keputusan Pembelian Pada Otto Coffe Truk Maumere - Ma’ruf, Muhamad Imam; Rengga, Andreas; Nunsio Handrian Meylano (Universitas Nusa Nipa Maumere, 2026)
This research aimed to: (1) describe purchasing decisions, price, and servicescape at Otto Coffee Truck Maumere, and (2) analyze the influence of price and servicescape on purchasing decisions at Otto Coffee Truck Maumere. This research used a quantitative approach using a survey method. Data collection techniques included observation, and the distribution of questionnaires to descriptive analysis, instrument testing, classical assumption testing, multiple linear regression analysis, partial testing (t-test), simultaneous testing (F-test), and the coefficient of determination (R2) with the assistance of statistical software. The Result of the research indicated that price had a positive but insignificant effect on purchasing decisions at Otto Coffee Truck Maumere. Meanwhile, the servoicescape variable had a positive and significant effect on purchasing decisiond. Simultaneously, price and servicescape had a positive and significant effect on purchasing decisions at Otto Coffee Truck Maumere. Therefore, Otto Coffee Truck Maumere should maintain a competitive pricing strategy and continue to improve the quality of uts servicescape to enhance consumers’ purchasing decisions.